2021
DOI: 10.1007/s00436-021-07050-w
|View full text |Cite
|
Sign up to set email alerts
|

Human and animal cystic echinococcosis in Konya, Turkey: molecular identification and the first report of E. equinus from human host in Turkey

Abstract: Cystic echinococcosis is a neglected, zoonotic disease in Turkey. The disease is commonly seen in rural areas where the local population is in close contact with livestock and dogs. This research aimed to molecularly identify of hydatid cysts in cattle and human isolates from Konya, Turkey. Following sample collection, direct microscopy was performed. After direct examination, total DNA was extracted, and positive PCR products of cox 1 mitochondrial gene (~875 bp) were sequenced. A total of 83 hydatid cysts (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…The fertility rate of hydatid cysts was higher in the liver of sheep, whereas in camels and goat, fertile cysts were mostly found in lungs. Some studies have reported more fertility in the liver [16,20,[38][39][40], and some studies reported more fertility in the lung [41][42][43][44]. In this study, it was found that none of the cysts from the cattle were fertile.…”
Section: Discussionmentioning
confidence: 49%
“…The fertility rate of hydatid cysts was higher in the liver of sheep, whereas in camels and goat, fertile cysts were mostly found in lungs. Some studies have reported more fertility in the liver [16,20,[38][39][40], and some studies reported more fertility in the lung [41][42][43][44]. In this study, it was found that none of the cysts from the cattle were fertile.…”
Section: Discussionmentioning
confidence: 49%
“…Further, there have been many reports indicating the presence of E. equinus in different intermediate hosts worldwide (Thompson and McManus, 2002;Boufana et al, 2012). E. equinus has been detected in humans, mules and donkeys in Turkey (Simsek and Cevik, 2014;Kesik et al, 2019;Macin et al, 2021). This study is the first report of E. equinus from stray dogs in Turkey.…”
Section: Discussionmentioning
confidence: 61%
“…Main IH and DH contributing to the maintenance of the parasite life cycle are equids and dogs. This species was thought not to be zoonotic for long until two cases of human infection were recently documented in Turkey and Uzbekistan [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%